Looking beyond parity: Gender wage gaps and the leadership labyrinth in the Canadian healthcare management workforce. Issue 1 (January 2023) - Gupta, Neeru; Balcom, Sarah Ann; Singh, Paramdeep
It is important for health organizations to monitor progress toward gender equity and inclusion goals among health human resources. Within the Canadian healthcare management workforce, however, recent investigations are lacking. This study examines gender differences in composition and compensation among health leadership in Canada using national census data. Findings show that although women represent over half (57%) of senior managers in health and social services, the pipeline from middle management (72%) suggests persistent career barriers disproportionately affect women. Women health and social care managers' earnings averaged 0.83-.89 for every dollar that a man earned. The gender wage gap remained statistically significant, with women health managers earning 12-20% less than men, after adjusting for age, education and other characteristics. Dynamic decomposition analyses highlighted that most of the gender wage gap could not be explained within the available data—a finding attributable, at least in part, to (unmeasured and unmeasurable) gender discrimination.